Reversion by ozone treatment of acute nephrotoxicity induced by cisplatin in rats - Ricardo González; Aluet Borrego; Zullyt Zamora; Cheyla Romay; Frank Hernández; Silvia Menéndez; Teresita Montero; Enis Rojas (Mediators of Inflammation)
BACKGROUND: Ozone therapy has become a useful treatment for pathological processes, in which the damage mediated by reactive oxygen species is involved. Several lines of evidence suggest that cisplatin-induced acute nephrotoxicity is partially mediated by reactive oxygen species.